Scope of Homoeopathic Treatment in Migraine- A Review (Homoeopathy for All, 2023)
Migraine causes a significant illness to  the sufferers and it is more prevalent  among women than men. Homoeopathic  medicines help in reducing the intensity  and frequency of the migraine attack. This  article presents indications of commonly  indicated homoeopathic medicines for  migraine with their differential indications.
Keywords: prevalent; illness; attack